Improved detection of melanoma metastases by iodine maps from dual energy CT. Issue 90 (May 2017) - Uhrig, Monika; Simons, David; Bonekamp, David; Schlemmer, Heinz-Peter
Graphical abstract: Highlights: Iodine maps from dual-energy CT provide high contrast-visualization of enhancing lesions. Iodine maps improve detection of metastases in staging examinations of melanoma patients. Iodine maps improve particularly the detection rate of muscle metastases. Abstract: Objective: Metastatic disease in melanoma has an unpredictable nature with deposits in rare locations such as musculature. Dual energy CT (DECT) provides high contrast-visualization of enhancement by using spectral properties of iodine. Purpose of this study was to evaluate whether iodine maps from DECT improve lesion detection in staging examinations of melanoma patients. Methods: This retrospective study was approved by IRB and written informed consent was obtained from all patients. 75 contrast-enhanced DECT scans (thorax and abdomen) from 75 melanoma patients (n = 69 stage IV; n = 6 stage III) were analysed. For each patient, conventional CT and iodine maps were reviewed independently by two radiologists. The number of lesions detected by reviewing the iodine maps following conventional CT was recorded. Unweighted Cohens Kappa coefficient ( κ ) was used for concordance analysis, Wilcoxon test for comparing lesion detection rates. Results: In 26 patients, at least one reader found additional lesions on iodine maps (inter-reader agreement 89%, κ  = 0.74 (0.742–0.747)). Compared to grey-scale images, mean detection rate for metastases improved from 86% (range 82–90) to 94% (90–99%) (p ≤ 0.01), for muscle metastases from 8% (8-8%) to 99% (98–100%) (p ≤ 0.06). Findings included 2 pulmonary emboli. Conclusion: Iodine maps from DECT improve detection of metastases, especially muscle metastases, and relevant findings in staging examinations of melanoma patients.